Perception of Collaborative Methodologies in Public Works in the Provincial Municipality of Puno - Huaricallo Vilca, Yvan (2023)
This research seeks to determine the perception of collaborative methodologies in the Provincial Municipality of Puno to guarantee adequate public investment, where a survey was used as an instrument to measure the perception of the levels of knowledge of collaborative methodologies. Officials and public servants involved in the design, execution and supervision of works were the target audience. It was determined that all the works carried out in the 2017-2021 period present term extensions, but not all the works present additional works.The perception of knowledge and use of collaborative software is high among civil servants and public servants involved in investment projects.Low communication is perceived between the design, execution and supervision offices, this concurrent problem responds to the fact that all officials do not want to have more work than they already count, municipal workers rely on Municipal management instruments such as the MOF and ROF.